Indoor Power Attenuation Model of Ultrawideband Waves - Andreyev, Yu. V.; Petrosyan, M. M. (Journal of communications technology & electronics, 2023)
To study the propagation of an indoor ultrawideband wave, a model with paired reflections from surfaces located opposite each other is proposed. It is shown that, in contrast to open areas, the multipath environment of premises is close to free space in terms of the character of wave attenuation with distance. Due to this, the energy reserve of an ultra-wideband communication line in a room should be higher than outdoors.